IMPLEMENTASI MODEL DIAMOND PORTER DALAM MEMBANGUN KEUNGGULAN BERSAING PADA KAWASAN AGROWISATA KEBUN BELIMBING NGRINGINREJO BOJONEGORO - Ety Saraswati; Aleria Irma Hatneny; Andi Normala Dewi (MAGISTER MANAJEMEN UNISMA, 2020)
This study aims to examine the competitive advantage analysis through the Porter’s diamond model in Agrotourism Ngringinrejo Bojonegoro. The research method used is descriptive with qualitative approach. Data collection techniques are done by interview, observation and documentation. The results showed important determinant in the competitive advantage of Agrotourism Ngringinrejo Bojonegoro, in accordance with the diamond porter model, consist of factor conditions; demand conditions; firms structure, strategy and competition; related and supporting industries; and government roles. The difference of each determinant of competitive advantage has implications for sustainability advantages which based on four main dichotomies, consist of government involvement, ownership structure, market (which is entered by the industry), and expansion of other areas that are not controlled (urban sprawl). The generic strategy formulation that is suitable for Agrotourism Ngringinrejo is a focus strategy, by building capacity to carry out innovations and research beyond increasing agricultural productivity, as well as building artificial tourism facilities to support competitiveness.Keywords: Tourism Competitive Advantage Models, Sustainable Competitive Advantage, Generic Strategies